EXPERIMENTAL INVESTIGATION OF GASOLINE FUEL EVAPORATION AT HIGH TEMPERATURES WITHIN TANK TRUCKS - Abdullah Kadhim Khudhair (Journals Park Publishing, 2025)
This study provides an experimental simulation of the evaporation from the gasoline fuel in truck-tanks, which are subjected to high-temperature summer weather-like conditions, such as those found in Iraq. A 50 L capacity stainless-steel tank of controlled environment with 20 L commercial RON 95 gasoline content was used to analyze the thermal loading impact on fuel vapor pressure, mass loss and volumetric changes in three different temperatures (30, 50 and 70 °C). Mission measurements recorded over a 6 h period have shown a strong positive relationship between temperature and evaporative losses; vapor pressure increased from 30 to 80 kPa and mass loss, for example, rose from 50 g to 225 g and volume loss increased from approximately.062 L to.27 L. These results illustrate the exponential effect of thermal stresses on gasoline, indicating that it is possible for tank-truck fuel to become dangerously pressurized and experience considerable financial loss when exposed to high temperatures. The results emphasize the importance for enhanced thermal management, insulation and safety facilities in fuel transfer systems where hot climates are prevailing.
Keywords: Gasoline Fuel Evaporation, High Temperatures, Tank Trucks.